Interaction and Perception of Interaction with 3D Objects during Design Activities. (May 2022) - Vuletic, T.; Duffy, A.; McTeague, C.; Hay, L.; Campbell, G.; Grealy, M.
Abstract: Post study questionnaires are used in design studies to uncover data about design reasoning and intent. A study was conducted where activities the study participants performed were compared to the participants' statements about those activities, collected immediately after the study via a questionnaire. The goal was to explore the reliability of post study evaluations. Disagreements between performed and reported activities were identified, and recommendations made to, where possible, include more objective measures of design activity.